2013
DOI: 10.1038/bjc.2013.204
|View full text |Cite
|
Sign up to set email alerts
|

Are the UK oncology trainees adequately informed about the needs of older people with cancer?

Abstract: Background:Outcomes for older people with cancer are poorer in the United Kingdom compared with that in other countries. Despite this, the UK oncology curricula do not have dedicated geriatric oncology learning objectives. This cross-sectional study of UK medical oncology trainees investigates the training, confidence level and attitudes towards treating older people with cancer.Methods:A web-based survey link was sent to the delegates of a national medical oncology trainee meeting. Responses were collected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…However, most medical oncologists have never received specific training on the particular needs of older people with cancer (Kalsi et al . ) and elderly patients have reported that their individual situation, including concurrent diseases and psychosocial status should receive more attention in the treatment decision‐making process (Bostkankervereniging Nederland ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most medical oncologists have never received specific training on the particular needs of older people with cancer (Kalsi et al . ) and elderly patients have reported that their individual situation, including concurrent diseases and psychosocial status should receive more attention in the treatment decision‐making process (Bostkankervereniging Nederland ).…”
Section: Introductionmentioning
confidence: 99%
“…Tailoring of care is needed, based on a thorough evaluation of the patient's overall health status in addition to tumour characteristics and the patient's preferences. However, most medical oncologists have never received specific training on the particular needs of older people with cancer (Kalsi et al 2013) and elderly patients have reported that their individual situation, including concurrent diseases and psychosocial status should receive more attention in the treatment decision-making process (Bostkankervereniging Nederland 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Oncologists have also been found to have had limited preparation for the task. In a survey of 64 oncology trainees in the UK, two‐thirds (66%) had received no training in the needs of older people with cancer . Best practice in the assessment and supportive care of elderly people with dementia might usefully be adapted to the context of cancer care, facilitating treatment and aiding with the management of cancer symptoms and treatment side effects.…”
Section: Discussionmentioning
confidence: 99%
“…As displayed by this survey, in neuro oncology clinics this is yet to occur with 80% of respondents not performing a cognitive or frailty test routinely. The reasons for this are likely multifactorial including a lack of time and awareness [10] but a key aspect may be the lack of a standardised and well validated tool for this cohort. The need for geriatric assessment screening tools within neuro oncology is validated by the participants, 50% of whom who felt a screening assessment changed their decision making half of the time.…”
Section: Discussionmentioning
confidence: 99%